Analisis Pengaruh Penerapan Tata Kelola Terhadap Kinerja Keuangan Pada Bank Syariah di Indonesia - Tri Auri Yanti (Jurnal Manajemen, Ekonomi, Keuangan dan Akuntansi, 2020)
This paper aims to find out the analysis of the effect of the application of governance on financial performance in Islamic banks in Indonesia. Good Corporate Governance is a Bank governance that applies the principles of transparency, accountability, responsibility, independence and fairness. Based on this, this research is seen from the financial performance of Islamic Commercial Banks in 2016-2019. This study uses secondary data obtained from the Sharia Banking Statistics Financial Services Authority (OJK) according to each bank. The variables in this study are Good Corporate Governance (X) and financial performance (Y). T test analysis results show that Good Corporate Governance has a positive and significant effect on financial performance. While the Determination Coefficient (R2) in Adjusted R2 is 0.156 which means that the financial performance of Islamic Commercial Banks can be explained by the independent variable by 15.6% and the rest is influenced by other variables